Modeling multi-stakeholder forest management: the case of forest plantations in Sabah - Guizol, P.; Purnomo, H. (International Rice Research Institute, 2005)
This paper proposes a framework to link social, economic, and biophysical dynamics using multi-agent simulation to explore scenarios of collaboration for forest plantation management. The modeling is based on decision theories. The purpose of this modeling is to produce shared knowledge about dynamics to facilitate coordination among stakeholders; its learning tool about forest management. The main hypothesis is that stakeholders, by creating a virtual world with researchers, will leran about the effects that their own decisions might have on themselves, others, and the environment. In the case of Sabah, it is at the stage of the first loop of learning, and scenarios need to be further tested with the stakeholders themselves. This forest plantation simulation suggests that the development of sawmills adapted to plantation wood might offer a promising pathway for increasing added value and the benefits of many stakeholders, including local communities.